Integrated focal psychotherapy: Results from a retrospective study - Gislon, Maria Clotilde; Sattin, Davide; Cis, Mattia; Fiaschi, Mara; Tognasso, Giacomo; D’Ambrosio, Vincenzo; Villa, Maria; Ruffino, Milena; Bergamaschi, Susanna (Frontiers in Psychology, 2023)
Background: Focus-Based Integrated Model (FBIM) is a form of psychotherapy grounded in inte-grating the psychodynamic and cognitive psychotherapy and Erikson’s life cycle model. Although there are many studies in the literature regarding the effectiveness of integrated models of psychotherapy, there is a paucity of research to establish the efficacy of FBIM. Objective: This pilot study aims to explore the effectiveness of the FBIM model by testing changes that occurred after FBIM therapy concerning individual well-being, presence/absence of symptoms, and general life functioning. Methods: Seventy-one participants were enrolled at the CRF Zapparoli Centre in Milan, 66.2% were female (N=47) with a mean age of the total sample equal to 35.2 years (SD = 12.8). We used the Clini-cal Outcomes in Routine Evaluation Outcome Measure (CORE-OM) to test treatment effectiveness. Results: The results highlighted that participants improved in all the four dimensions of CORE-OM (Well-being, Symptoms, Life functioning and Risk), that females improved more than males and that in most of the cases (64%), the change obtained was clinically reliable. Conclusion: The FBIM model seems to be effective for treating several patients. Most of the partici-pants have seen significant changes in symptoms, life functioning, and general well-being.